PENGEMBANGAN MEDIA PEMBELAJARAN BONEKA TABLET UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA SISWA KELAS I SEKOLAH DASAR NEGERI 27 GERNIS - Evi Nur Islamiyati; Indri Astuti; Juhana Juhana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to develop tablet puppet learning media to improve reading skills in first grade elementary school students. The research was conducted using the Research and Development method with the ADDIE development model through the analyze, design, development, implementation and evaluation stages. The research was conducted at 27 Gernis Public Elementary School in grade 1 with 70 participants. The tablet dummy media developed was validated by 2 material experts with an average score of 4.80 in the "valid" category, 2 design experts with an average score of 75 in the "valid" category, and 2 media experts with an average score of 4.86 in the "valid" category. ”. The results of the analysis were carried out by empirical tests including individual tests, small group tests, and large group tests each showing a "very good" attitude in using tablet puppet learning media. The test for the effectiveness of media use was carried out by a gain score test with a value of 0.71 in the "High" category. Based on the results of this analysis, it can be concluded that tablet puppet learning media can be applied to improve reading skills in grade 1 elementary school students.